Helical Molecular Springs with Varying Spring Constants. (9th November 2022) - Murphy, Kyle E.; McKay, Kyle T.; Schenkelberg, Mica; Sharafi, Mona; Vestrheim, Olav; Ivancic, Monika; Li, Jianing; Schneebeli, Severin T.
Abstract: We report a general synthetic route toward helical ladder polymers with varying spring constants, built with chirality‐assisted synthesis (CAS). Under tension and compression, these shape‐persistent structures do not unfold, but rather stretch and compress akin classical Hookean springs. Our synthesis is adaptable to helices with different pitch and diameter, which allowed us to investigate how molecular flexibility in solution depends on the exact geometry of the ladder polymers. Specifically, we showed with molecular dynamic simulations and by measuring the longitudinal 1 H NMR relaxation times ( T 1 ) for our polymers at different Larmor frequencies, that increasing the helix diameter leads to increased flexibility. Our results present initial design rules for tuning the mechanical properties of intrinsically helical ladder polymers in solution, which will help inspire a new class of robust, spring‐like molecular materials with varying mechanical properties. Abstract : Minature versions of Hookean springs can be built from single‐handed helical ladder polymers. The spring constants of these molecular springs vary with the helix diameter analogous to classical springs. These new molecular springs provide an alternative mechanism of expansion/contraction controlled by the intrinsic helical geometries of the ladder polymers, which do not unfold under tension unlike more common flexible polymers.